Łukasz Szulc, Transnational Homosexuals in Communist Poland. Cross-Border Flows in Gay and Lesbian Magazines, New York: Palgrave Macmillan 2018, ss. 253, ISBN 978-3-319-58900-8. - Burszta, Jędrzej (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2019)
Recenzja pracy naukowej: ŁUKASZ SZULC, Transnational Homosexuals in Communist Poland. Cross-Border Flows in Gay and Lesbian Magazines, New York: Palgrave Macmillan 2018, ss. 253, ISBN 978-3-319-58900-8.